The quality of life of the elderly is negatively affected by pertrochanteric femoral fractures: a comparative study - Yaradılmış, Yüksel Uğur; Okkaoglu, Mustafa Caner; Özdemir, Erdi; Ateş, Ahmet; Demirkale, İsmail and Altay, Murat (The European Research Journal, 2022)
Objectives: Limited data is available regarding the quality of life of hip fracture patients following surgery. This study examined the mid-term quality of life of hip fracture patients and compared these patients with healthy elderly patients devoid of hip fractures. Methods: A total of 103 patients (aged > 65 years) with pertrochanteric femoral fractures were treated with proximal femoral nail surgery in our clinic between January 2012 and December 2016. A healthy control group (n = 100) was demographically matched to the patients. The final follow-up visit included their Harris Hip Score and completion of a Short Form-36. The eight sub-parameters from the Short Form-36 form were also assessed. Results: The mean follow-up time for the patients was 36.4 ± 12.3 (range, 24-72) months. The mean Charlson comorbidity score for the patient group was 4.4 ± 2.1 and the mean Harris Hip Score was 77.24 ± 10.2. The comparison of the Short Form-36 sub-parameters revealed that the quality of life of the patient group was found to be lower than that of the control group for the following parameters physical function, physical roles, vitality, and social function (p < 0.05). Conclusions: Even if the fracture had healed of patients with hip fractures, QoL related to physical and social functions was not improved accordingly, new healthcare policies should be developed for these patients based on the premise that their physical capacity may not be fully regained. Moreover, the importance of hip fracture prevention was demonstrated by this study.